Tomographic, Histological, and Immunohistochemical Evidences on the Use of N-Butyl-2-Cyanoacrilate for Onlay Graft Fixation in Rabbits - Oliveira Neto, Patricio José DE; Cricchio, Giovanni; Hawthorne, Ana Carolina; Okamoto, Roberta [UNESP]; Sennerby, Lars; Lungren, Stefan; Salata, Luiz Antonio (Wiley, 2012)
Background: The bone tissue responses to Cyanoacrylate have been described in the literature, but none used N-butyl-2-cyanoacrilate (NB-Cn) for bone graft fixation. Purpose: The aims of the study were: (a) to analyze the bone grafts volume maintenance fixed either with NB-Cn or titanium screw; (b) to assess the incorporation of onlay grafts on perforated recipient bed; and (c) the differences of expression level of tartrate-resistant acid phosphatase (TRAP) protein involved in bone resorption. Materials and Methods: Eighteen New Zealand White rabbits were submitted to calvaria onlay grafting on both sides of the mandible. On one side, the graft was fixed with NB-Cn, while on the other hand the bone graft was secured with an osteosynthesis screw. The computed tomography (CT) was performed just after surgery and at animals sacrifice, after 1 (n=9) and 6weeks (n=9), in order to estimate the bone grafts volume along the experiments. Histological sections of the grafted areas were prepared to evaluate the healing of bone grafts and to assess the expression of TRAP protein. Results: The CT scan showed better volume maintenance of bone grafts fixed with NB-Cn (p≤0.05) compared with those fixed with screws, in both experimental times (analysis of variance). The immunohistochemical evaluation showed that the TRAP expression in a 6-week period was significantly higher compared with the 1-week period, without showing significant difference between the groups (Wilcoxon and Mann-Whitney). Histological analysis revealed that the NB-Cn caused periosteum damage, but provided bone graft stabilization and incorporation similar to the control group. Conclusion: The perforation provided by screw insertion into the graft during fixation may have triggered early revascularization and remodeling to render increased volume loss compared with the experimental group. These results indicate that the NB-Cn possesses equivalent properties to titanium screw to be used as bone fixation material in osteosynthesis. © 2010 Wiley Periodicals, Inc.
Keywords: Bone graft fixation; Cyanocrylate; Healing bone; Histologic evaluation; Immunohistochemistry; Onlay bone graft; Tomographic evaluation